Assessing Learning Preferences of Tertiary Education Students in Jordan Post COVID-19 Pandemic and the Associated Perceived Stress - Iman A. Basheti; Thafer Yusif Assaraira; Nathir M. Obeidat; Fawwaz Al-a; Mashhoor Refai (MDPI AG, 2022)
Background: The COVID-19 pandemic was associated with extensive lockdown strategies which included universities, forcing educational administrations to implement online learning and acknowledging the countless consequences it would have on the educational process. Those prompt changes highlighted the importance of online learning effects on educational outcomes. Aim: To assess students' learning preferences and the stress associated with online and face-to-face learning. Methods: This is a multi-center cross-sectional study, employing a web-based Google Forms, which was conducted among four universities in Jordan. The survey assessed students' demographic characteristics, educational methods received, assessment of factors that may have influenced students' stress, and assessment of 'stress' using the Perceived Stress Scale (PSS). Results: Among 1241 participating students, most of the students preferred face-to-face learning (43.3%), although the majority believed that online learning is less stressful (42.2%). The majority believed that face-to-face learning is efficient (42.7%), and that online learning is moderately efficient (38.4%), while many (35.3%) reported that the future of learning will be blended 50/50 between online and face-to-face learning. The mean score of PSS was 20.88, with 62.9% reported to have experienced moderate perceived stress, and 22.4% experienced high perceived stress. Conclusions: Although Jordanian university students prefer face-to-face learning over online learning, they believe that online learning can be less stressful. In addition to that, Jordanian students experienced a high mean of the PSS score, with more than 20% of students reporting high perceived stress.